SHA-1 and MD5 Cryptographic Hash Functions: Security Overview - Roman Jasek (Communications - Scientific letters of the University of Zilina, 2015)
Despite their obsolescence and recommendations they are phased out from production environment, MD5 and SHA-1 cryptographic hash functions remain defaults frequently offered in many applications, e.g., database managers. In the article, we present a security overview of both algorithms and demonstrate the necessity to abandon them in favor of more resilient alternatives due to low computational requirements necessary to reverse engineer the message digests, or to future proof security due to advances in hardware performance and scalability. Suitability procedures and their methods of use are part of this article.